Risk of Noncontact Anterior Cruciate Ligament Injuries Is Not Associated With Slope and Concavity of the Tibial Plateau in Recreational Alpine Skiers: A Magnetic Resonance Imaging–Based Case-Control Study of 121 Patients. (June 2016) - Blanke, Fabian; Kiapour, Ata M.; Haenle, Maximilian; Fischer, Jens; Majewski, Martin; Vogt, Stephan; Camathias, Carlo
Background: Anatomic features of the tibial plateau (ie, posterior slope and medial concavity) have been associated with an increased risk of anterior cruciate ligament (ACL) injuries. However, it remains unclear whether these findings translate to ACL injuries sustained during recreational alpine skiing. Purpose: To investigate the association in recreational alpine skiers between prominent morphological features of the tibial plateau (slope and concavity) and the risk of sustaining an ACL injury during a noncontact incident. Study Design: Case-control study; Level of evidence, 3. Methods: Magnetic resonance imaging data of 121 recreational alpine skiers (74 female, 47 male) after a noncontact knee injury were used for this study. Of these patients, 80 (71% female [n = 57]) had a complete unilateral ACL tear (rupture group), and 41 (41% female [n = 17]) had no indications of an ACL injury (intact group). Two blinded independent examiners measured the slopes of the tibial plateau in the sagittal and coronal planes along with the maximum depth of the medial tibial plateau. Measurements were compared between sexes and between groups using t tests. Logistic regression was used to assess the associations between quantified anatomic indices and the risk of ACL injuries. Results: Within 121 study patients, female skiers had greater odds of an ACL tear compared with male skiers (odds ratio, 3.5; 95% CI, 1.6-7.8; P < .001). Female skiers were more likely to have a greater lateral tibial slope (LTS) ( P = .02) and medial tibial slope (MTS) ( P = .02) with a shallower medial tibial depth (MTD) ( P = .02) compared with male skiers. No differences between sexes were observed in the coronal tibial slope (CTS) ( P = .97). Male and female skiers as a combined group showed no associations between quantified anatomic indices and the risk of sustaining an ACL tear ( P > .10). Likewise, no significant differences were observed between the intact versus rupture group in any of the quantified anatomic indices ( P > .10). Similar findings were observed when the analyses were repeated on male and female skiers separately. Conclusion: Despite differences between sexes in knee anatomy and the injury risk, the sagittal and coronal slopes (LTS, MTS, CTS), as well as the concavity of the medial tibial plateau (MTD), were not associated with the risk of an ACL tear during a noncontact injury among recreational alpine skiers.